The Relationship Between School Climate, Traditional Bullying, Cyberbullying and Self-Esteem Among Secondary School Students in Albania - Peppo, Jonida; Lame, Edvin; Katsarou, Dimitra V. (European Journal of Social Science Education and Research, 2026)
Bullying, including traditional and cyber forms, represent a persistent psychosocial challenge within school environments and is associated with adverse psychological outcomes among adolescents. School social climate and self-esteem are recognized as key contextual and individual factors influencing bullying involvement. However, empirical evidence from Southeast European countries remains limited. This paper aims to examine the relationships among school social climate, traditional bullying, cyberbullying and self-esteem among secondary school students in Albania, with particular emphasis on the protective role of school climate. A cross-sectional correlational design was employed using a nationally representative sample of 1,056 adolescents from 42 lower and upper secondary schools across Albania. Data were collected using validated measures of school social climate, traditional bullying, cyberbullying and self-esteem. School social climate was positively associated with adolescents’ self-esteem and negatively associated with traditional bullying and cyberbullying. Bullying involvement was consistently associated with lower self-esteem. A positive school social climate functions as a protective factor against bullying involvement and diminished self-esteem. School-based interventions aimed at strengthening school climate and adolescents’ self-esteem may contribute meaningfully to bullying prevention and psychological well-being.